Sourdough fermentation of carob flour and its application in wheat bread - Novotni, Dubravka (Array, 2021)
Research background. Carob is widely cultivated Mediterranean plant, but its flour is scarcely used in bread making. Previous studies investigated the quality of wheat bread with added carob flour showing discrepant results. This study aims to investigate the fermentation performance, antioxidant activity, rheological behaviour and baking application of carob sourdough. Experimental approach. Carob sourdough was fermented with Lactobacillus brevis or Lactobacillus fermentum combined with Saccharomyces cerevisiae for 24 h at 30 °C. At the end of sourdough fermentation, number of viable lactic acid bacteria and yeast cells, total titratable acidity, pH value, antioxidant activity, phenolics and sugar content were determined. Carob flour (12 % flour mass fraction) or sourdough equivalent (22.5 % dough mass fraction) was applied in making composite partially baked frozen bread. Dough rheology was monitored using a farinograph. Nutritive value, physical properties and sensory attributes of the rebaked bread samples were evaluated using a hedonic test. Results and conclusions. By the end of fermentation, carob sourdough reached pH=4.2– 4.5 and total acidity 9.9–12.3 mL of 0.1 M NaOH, sugar content on dry mass basis was reduced by 8 g/100 g, while total phenolics and antioxidant activity were increased up to 21 %, depending on the starter culture. Addition of carob flour or sourdough to wheat dough resulted in firmer consistency, longer development time, and lower quality number. Regardless, bread with carob flour had significantly improved specific volume. Compared with common wheat bread, carob bread had increased dietary fibre content (46 %), total phenolics (140–200 %) and antioxidant activity (240 300 %), higher shape, larger volume, reduced crumbliness, unchanged firmness and darker crumb colour.